Non‐Topotactic Transformation of Silicate Nanolayers into Mesostructured MFI Zeolite Frameworks During Crystallization. Issue 19 (5th April 2017) - Berkson, Zachariah J.; Messinger, Robert J.; Na, Kyungsu; Seo, Yongbeom; Ryoo, Ryong; Chmelka, Bradley F.
Abstract : Mesostructured MFI zeolite nanosheets are established to crystallize non‐topotactically through a nanolayered silicate intermediate during hydrothermal synthesis. Solid‐state 2D NMR analyses, with sensitivity enhanced by dynamic nuclear polarization (DNP), provide direct evidence of shared covalent 29 Si‐O‐ 29 Si bonds between intermediate nanolayered silicate moieties and the crystallizing MFI zeolite nanosheet framework.